Could diabetes prevention programmes result in the widening of sociodemographic inequalities in type 2 diabetes? Comparison of survey and administrative data for England - Peter Bower; Claudia Soiland-Reyes; Carole Bennett; Lisa Brunton; Patrick Burch; Elaine Cameron; Tarani Chandola; Georgia Chatzi; Sarah Cotterill; David P French; Judith Gellatly; Mark Hann; et al. (Health and Social Care Delivery Research, 2025)
This article consists of a citation of a published article describing research funded by the Health and Social Care Delivery Research programme under project number 16/48/07, and is provided as as part of the complete record of research outputs for this project. The original publication is available at: https://doi.org/10.1136/jech-2022-219654 Background The NHS Diabetes Prevention Programme (DPP) in England is a behavioural intervention for preventing type 2 diabetes mellitus (T2DM) among people with non-diabetic hyperglycaemia (NDH). How this programme affects inequalities by age, sex, limiting illnesses or disability, ethnicity or deprivation is not known. Methods We used multinomial and binary logistic regression models to compare whether the population with NDH at different stages of the programme are representative of the population with NDH: stages include (1) prevalence of NDH (using survey data from UK Household Longitudinal Study (n=794) and Health Survey for England (n=1383)); (2) identification in primary care and offer of programme (using administrative data from the National Diabetes Audit (n=1 267 350)) and (3) programme participation (using programme provider records (n=98024)). Results Predicted probabilities drawn from the regressions with demographics as each outcome and dataset identifier as predictors showed that younger adults (aged under 40) (4% of the population with NDH (95% CI 2.4% to 6.5%)) and older adults (aged 80 and above) (12% (95% CI 9.5% to 14.2%)) were slightly under-represented among programme participants (2% (95% CI 1.8% to 2.2%) and 8% (95% CI 7.8% to 8.2%) of programme participants, respectively). People living in deprived areas were under-represented in eight sessions (14% (95% CI 13.7% to 14.4%) vs 20% (95% CI 16.4% to 23.6%) in the general population). Ethnic minorities were over-represented among offers (35% (95% CI 35.1% to 35.6%) vs 13% (95% CI 9.1% to 16.4%) in general population), though the proportion dropped at the programme completion stage (19% (95% CI 18.5% to 19.5%)). Conclusion The DPP has the potential to reduce ethnic inequalities, but may widen socioeconomic, age and limiting illness or disability-related inequalities in T2DM. While ethnic minority groups are over-represented at the identification and offer stages, efforts are required to support completion of the programme. Programme providers should target under-represented groups to ensure equitable access and narrow inequalities in T2DM. Funding This publication was funded by the Health and Social Care Delivery Research programme as a part of award number 16/48/07. DOI https://doi.org/10.1136/jech-2022-219654 This article reports on one component of the research award Evaluating the NHS Diabetes Prevention Programme (NHS DPP): the DIPLOMA research programme (Diabetes Prevention Long term Multimethod Assessment). For more information about this research please view the award page [https://fundingawards.nihr.ac.uk/award/16/48/07]